Multimodal communication of corporate website design - Hassan, Hanita (Penerbit UTM, 2012)
This book examines the multinational corporate website designs from a communication perspective. It looks at the ways in which different multimodal modes are employed in disseminating information to customers. How persuasive is a corporate website? How multimodal modes are used to portray the company identity and ideology? How can a particular website design depict self–presentation? This book attempts to show that the aim of corporate websites is not restricted to promoting products but the roles of the websites are inclusive of building brand image, portraying the company identity and promoting their ideology.